The competitive cross-country skier - an impressive human engine - Holmberg, H. C. (Science and Skiing IV, 2009)
Cross-country skiing is one of the most demanding endurance Sports. It imposes extensive physiological challenges due to the perpetual changes between, and utilisation of, different skiing techniques, each involving the upper and lower body to various extents. Altogether, the uniqueness of the sport has over the years contributed to significant interest from physiologists in their ongoing ambition to understand more about the human engine.